Farmers Sued Over Deleted Climate Data. So the Government Will Put It Back. - Zraick, Karen (The New York Times, 2025)
The Agriculture Department pledged to restore online climate information that farmers said helped them do business, but which officials had deleted.
United States of America
Keywords: Agriculture Department; Agriculture and Farming; Clayton; Walter J; Environmental Working Group; Global Warming; Greenhouse Gas Emissions; Natural Resources Defense Council; Northeast Organic Farming Assn; Suits and Litigation (Civil); United States Politics and Government